PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI NON AKADEMIK DI IAIN MADURA KABUPATEN PAMEKASAN - Syaiful Rachman, Syaiful Rachman; Chamariyah, Chamariyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
Abstract This research was conducted at the Madura IAIN Campus in Pamekasan Regency with a total sample of 62 people (sampling technique was random sampling). The objectives of this study are: 1). Describe and analyze leadership style, motivation, competence and non-academic employee performance at IAIN Madura in Pamekasan Regency, 2). To test and analyze whether leadership style, motivation and competence simultaneously have a significant influence on the performance of non-academic employees at IAIN Madura in Pamekasan Regency, 3). To test whether leadership style, motivation and competence partially have a significant effect on the performance of non-academic employees at IAIN Madura in Pamekasan Regency, 4). To test which variables among leadership styles, motivations and competencies that have a dominant influence on the performance of non-academic employees at IAIN Madura in Pamekasan Regency. Analysis of data using SPSS, this type of research is explanatory research using a quantitative approach. The results of the study show that: 1). Simultaneously, leadership style, motivation and competence have a significant influence on the performance of non-academic employees at Madura IAIN in Pamekasan Regency, as evidenced by the calculated F value of 0.818 with a significance level of 0.04 (less than 0.05). 3). Partially, leadership style, motivation and competence have a significant influence on the performance of non-academic employees of IAIN Madura in Pamekasan Regency, leadership style is evidenced by the value of t count is 0.265 with a significance level of 0.02 (smaller than 0.05), then known work motivation with a t count value of 0.342 with a significance level of 0.03 positive and significant effect on the performance of non-academic employees at Madura IAIN in Pamekasan Regency (smaller than 0.05) and Competence has a positive and significant effect with a t count value of 1.413 with a level significance of 0.04 (less than 0.05).